PROBLEMS OF DEVELOPMENT OF SPACE ACTIVITY AND INTELLECTUAL PROPERTY - Боричевський, В. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the urgent issues of the development of space activity and the necessity in this context of solving problems of a legal nature, in particular the protection of intellectual property rights, is determined.